Changes in donor lymphocyte infusion for relapsed patients post-hematopoietic stem cell transplantation: a 30-year single-center experience - Uchibori, Yusuke; Kurosawa, Shuhei; Najima, Yuho; Haraguchi, Kyoko; Sadato, Daichi; Hirama, Chizuko; Sadaga, Yasutaka; Kondo, Kaori; Kato, Chika; Sakai, Satoshi; Kambara, Yasuhiro; Ouchi, Fumihiko; et al. (Frontiers in Immunology, 2025)
IntroductionDonor lymphocyte infusion (DLI) is a therapeutic approach for relapse after hematopoietic stem cell transplantation (HSCT). Despite their reported efficacy, the evolution of DLI practices over time remains underexplored.MethodsThis study provided a comprehensive analysis of DLI strategies and outcomes over 30 years at a single institution. A retrospective analysis was conducted on 75 patients who underwent DLI for disease relapse between April 1994 and March 2024. The primary endpoint was the 3-year overall survival (OS) rate after DLI. Secondary endpoints included the 100-day complete remission (CR) rate and incidence of acute graft-versus-host disease (GVHD).ResultsThe median age at the first DLI was 49 years (range, 20–69 years). The most common underlying diseases in all 75 cases were acute myeloid leukemia (AML, n = 46) and myelodysplastic syndromes (MDS, n = 12). Until 2014, DLI was only performed in patients with AML (n = 14), MDS (n = 2), or chronic myeloid leukemia (n = 5). However, since 2015, patients with various diseases, including lymphoid malignancies, have also undergone DLI. Azacitidine was the most frequently used combination therapy with DLI (n = 34). Regimens including venetoclax and FLT3 inhibitors have been commonly used since 2019 (n = 18). The 3-year OS rate was 29.1% (95% CI, 18.8–40.2%). Factors negatively influencing OS included age ≥50 years and a high or very high refined disease risk index. The 100-day CR rate was 52.1%, and acute GVHD occurred in 25.3% of the patients, with no strong correlation between GVHD incidence and CR achievement. Among 18 patients who underwent three or more DLIs since 2018, 88.9% achieved remission following DLI or second HSCT, with a median follow-up of 949.5 days for survivors.ConclusionThis study highlighted the evolving trends in DLI practices and the diversification of combination therapies. Future research should focus on further validating these findings and optimizing DLI protocols to improve patient outcomes.